MECHANISMS OF PROTEIN FOLDING AND MISFOLDING: BIOPHYSICAL INSIGHTS INTO NEURODEGENERATIVE DISEASES (Western European Journal of Medicine and Medical Science, 2026)
Protein folding the process by which polypeptide chains attain functional three-dimensional structures — is fundamental to all cellular processes. However, errors in this process, termed protein misfolding, are implicated in the pathogenesis of a wide range of neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), amyotrophic lateral sclerosis (ALS), and prion diseases. These disorders share a common hallmark: the aberrant accumulation of misfolded proteins that aggregate into toxic oligomers and insoluble fibrils, disrupting neuronal integrity and leading to progressive cognitive and motor decline. Biophysical mechanisms that govern folding and misfolding involve complex energy landscapes, thermodynamic stability, and proteostasis network dysfunctions. Recent studies reveal that misfolded proteins can propagate via seeding and prion-like mechanisms, amplifying pathological aggregates throughout the nervous system. This review examines the molecular basis of protein folding and misfolding, the pathophysiological roles of protein aggregates in neurodegenerative diseases, and current and emerging therapeutic strategies aimed at mitigating misfolding and aggregation